SAT-278 Vaginal Cabergoline: A Simple Solution to a Challenging Problem - Abuaisha, Munder (J Endocr Soc, 2020)
Introduction: Prolactinomas is a common endocrine disorder that can be associated with significant morbidity. Generally, prolactinomas are more responsive to pharmacologic treatment than any other types of pituitary adenoma. Dopamine agonists (DA), including cabergoline and bromocriptine, are the first line of treatment in all sizes of prolactinomas and they decrease both the secretion and size of these adenomas. However, treatment remains challenging for patients who are intolerance to those medications. Case: We report a 32-year-old Hispanic woman who presented with secondary amenorrhea, she was found to have hyperprolactinemia of 1496 mcg/L. MRI of the brain showed a pituitary adenoma measuring 2.7 cm with sella turcica invasion and mass effect on the optic chiasma. She failed the lowest doses of oral cabergoline and bromocriptine and underwent TSS and gamma knife radiosurgery. Given her persistent symptoms (marked depression, insomnia, fatigue, short-term memory loss, and lack of concentration along with constipation) and elevation of prolactin, she was started on low dose vaginal cabergoline leading to a marked improvement of her symptoms and a steady decrease in serum prolactin. Discussion: Despite the availability of DA as a first-line treatment of Prolactinoma, treatment remains challenging, given the commonly reported side effects for all DA. Cabergoline is oftentimes the treatment of choice due to efficacy and favorable side-effect profile. However, intolerance to those medications can lead to discontinuation of therapy and increase morbidity. Other strategies, including transsphenoidal surgery (TSS) or radiation therapy, have been considered for the minority of patients whose adenomas are resistant to DA or who cannot tolerate these drugs. Interestingly, tolerance to DA can be improved by administering the drug intravaginally, which can have similar efficacy to the oral route and a more favorable side-effect profile. However, only a few studies assessed the effectiveness and tolerance of vaginal DAs in hyperprolactinemic patients intolerant to oral medications, little evidence supports the use of intravaginal DA to improve drug tolerance, and further studies are necessary to determine the safety and efficacy of vaginal cabergoline.